PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MELALUI KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA TOKO NINA CEMILAN PRAJEKAN BONDOWOSO - Rosanti, Adelia Dwi; Arief, Muhammad Yahya; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2022)
Marketing is an activity that needs to be carried out by companies, both goods and services companies in an effort to maintain the viability of their business. The purpose of this study is to analyze and examine the effect of Product Quality on Purchase Decisions through Consumer Trust as an Intervening Variable. The population of this research is the consumer of Nina Cemilan in Prajekan Bondowoso. The sampling technique was determined by simple random sampling. For data analysis and hypothesis testing in this study using the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, which shows that Product Quality has a significant positive effect on Consumer Confidence, Product Quality has a significantly positive effect on Purchase Decisions, Consumer Trust has a significantly positive effect on Purchase Decisions, Product Quality on Purchase Decisions through Consumer Trust positive significant effect.